(Invited) Microcrystalline Silicon Based TFTs and Resistors for Reliable Flexible Electronics. (18th August 2016) - Kervran, Yannick; Kandoussi, Khalid; Dong, Hanpeng; Janfaoui, Sabri; Coulon, Nathalie; Simon, Claude; Jacques, Emmanuel; Mohammed-Brahim, Tayeb
Abstract : Silicon based flexible electronics is shown here as the right way when considering the reproducibility of the process and the long-term reliability, the only way leading to commercially available products. Microcrystalline silicon films are deposited directly on plastic substrates (PEN and Polyimide) at low temperature. Films are highly crystallized. Crystalline volume is higher than 73% for 50nm thick film as calculated from Raman spectra. Resistances and TFTs based on such silicon film are bent at lower radius than 1 mm without breaking. More than 200 times of such extreme bending are done without changing the TFT's characteristics